Seasonal Variation of Heavy metals in water samples from the Sitalakhya River - Islam, Muhammad Zakarul; Azim, Mohammad Alaul; Islam, Rafiqul; Quraishi, Shamshed B (Journal of Bangladesh Academy of Sciences, 2009)
The study was carried out to analyze the concentration of the trace heavy elements in water from five different stations of Sitalakhya river and was sampled every three months from December 4 to September 5. All the samples were analyzed for the determination of trace elements by using Atomic Absorption Spectrophotometry method. The concentration of iron, lead, cadmium, manganese, cobalt, nickel, chromium, zinc, copper ranged from 1.26 - 8.31, < 17.96 - 22.60, < 3.00 - 3.72, 29.38 - 197.33, < 4.05 - 7.91, < 10.66 - 23.84, < 4.05 - 9.57, 7.86 - 36.11 and 3.08 - 12.82 Î¼g/l. The concentration of different elements varied in different season and the maximum amount was observed in the dry season (March). The present study also revealed that although the pollution level is not alarming yet but it increasing slowly. The water quality characteristics were within the permissible level of Bangladesh standard and below the EPA and WHO standard except for iron. From this study it is clear that the water of this river is not an immediate threat to ecosystem but some parameters may gradually deteriorate with time and in future may cause a threat to ecosystem. doi: 10.3329/jbas.v32i1.2437 Journal of Bangladesh Academy of Sciences, Vol. 32, No. 1, 13-22, 2008